Pengaruh Kompensasi, Kesehatan Dan Keselamatan Kerja Terhadap Kinerja Karyawan Pada PT. Sinar Jaya Inti Mulya Kota Metro - Dupri, Muhammad Demsi; Sugeng, Sugeng; Andriani, Vivin (Jurnal Manajemen DIVERSIFIKASI, 2023)
The workforce plays a very big role in carrying out company activities, the existence ofhuman resources in a company plays a very important role. This research aims to analyze theinfluence of Compensation, Occupational Health and Safety on Employee Performance. Thisresearch was conducted at PT. Sinar Jaya Inti Mulya Metro City, Lampung. This researchuses quantitative methods. The data used is primary data obtained using a questionnairemethod for a sample using the Slovin formula, obtained as many as 121 employees at PT.Sinar Jaya Inti Mulya Metro City. The analysis tool used is Multiple Linear Regression withthe help of the SPSS 20.0 program. The research results show that 1) Compensation has apositive and significant influence on employee performance. 2) Health has a positive andsignificant influence on employee performance. 3) Work safety has a positive and significantinfluence on purchasing decisions. 4) Compensation, health and work safety have a positiveand significant influence together on employee performance. The coefficient of determinationvalue is 0.67, which means that the dependent variable can be explained by the independentvariable by 67%. This means that the independent variables include compensation,occupational health and safety at 67% while the remaining 33% is influenced by othervariables not examined in this research.